Ekowisata dan Wisata Religius sebagai Relasi antara Manusia, Alam dan Tuhan - Syihabul Furqon; Busro Busro; Abdul Syukur (Politeknik Pariwisata NHI Bandung, 2021)
The development of the world of tourism so rapidly from year to year. This implies an inevitable new tourist attraction. This development has its traces from the 20th century as a result of the decline of human existence, the objectification of nature and the breaking of the chain of sacredness with God through tradition. The second decade of the 21st century shows that this disconnection and decadence can be re-woven through tourism. This research will explore the statement: what kind of tourism model can then intertwine humans' disconnection from themselves, nature and God? The result is that in the ecotourism and religious tourism models there is a possibility of a harmonious mutualism symbiosis. Specifically in this study, the authors found that ecotourism (Trigonasantri Garden) and religious tourism objects (Petilasan Linggabuana) have a fundamental component—traditionally—relationship between humans, nature and God.